Do healthy lifestyle behaviors affect COVID-19 vaccination attitudes in Generation Z? - Barut, Sümeyye; Baransel, Esra Sabancı; Can, Aylin (My University, 2022)
This study was carried out to determine the effects of healthy lifestyle behaviors on the COVID-19 vaccine attitude in the Z generation. The descriptive cross-sectional\rstudy was conducted in Turkey using web-based questionnaires, and 510 participants (348 women, 162 men, age 15-24) in the Z generation. The data were collected\rby using Personal Information Form and Health Lifestyle Behaviors Scale-II (HLBS-II). It was determined that 89.4% of the female participants and 85.8% of the male\rparticipants, who participated in the study, had the COVID-19 vaccine. It was determined that 84.2% of the women who had the COVID-19 vaccine received the second\rdose, while 76.3% of the men had the second dose. It was determined that the mean scores of women and men who had COVID-19 vaccine, found the COVID-19 vaccines\rsafe, and believed that it was more beneficial than harm, had higher mean scores from HLBS-II and the difference between the groups was statistically significant (p<0.05).\rAs a result of this study, it was determined that the healthy lifestyle behavior levels of the Z generation have an effective role on the COVID-19 vaccine attitudes during\rthe COVID-19 pandemic process.
Keywords: Halk ve Çevre Sağlığı; Sağlık Politikaları ve Hizmetleri